2012
DOI: 10.1158/0008-5472.can-12-1824
|View full text |Cite
|
Sign up to set email alerts
|

Microdistribution and Long-term Retention of 239Pu (NO3)4 in the Respiratory Tracts of an Acutely Exposed Plutonium Worker and Experimental Beagle Dogs

Abstract: The long-term retention of inhaled soluble forms of plutonium raises concerns as to the potential health effects in persons working in nuclear energy or the nuclear weapons program. The distributions of long-term retained inhaled plutonium-nitrate [239Pu (NO3)4] deposited in the lungs of an accidentally exposed nuclear worker (Human Case 0269) and in the lungs of experimentally exposed beagle dogs with varying initial lung depositions were determined via autoradiographs of selected histologic lung, lymph node,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, while it enabled good fits to be made to the experimental data, including this bound fraction had little effect on dose. (838) More recent studies indicate the presence of a small, but very long-term, bound state for plutonium (e.g. James et al., 2007; Nielsen et al., 2012), which could potentially increase equivalent doses to the lungs significantly, particularly if it occurs in the BB and bb regions. Consideration is therefore only given here to such a long-term bound state.…”
Section: Plutonium (Z = 94)mentioning
confidence: 99%
“…However, while it enabled good fits to be made to the experimental data, including this bound fraction had little effect on dose. (838) More recent studies indicate the presence of a small, but very long-term, bound state for plutonium (e.g. James et al., 2007; Nielsen et al., 2012), which could potentially increase equivalent doses to the lungs significantly, particularly if it occurs in the BB and bb regions. Consideration is therefore only given here to such a long-term bound state.…”
Section: Plutonium (Z = 94)mentioning
confidence: 99%
“…The concentration of plutonium activity was not uniform in the various lung regions, but was significantly less than the average lung concentration in the bronchovascular interstitial tissue of the bronchi and the lumen of the conducting airway, and significantly higher in parenchymal and non-parenchymal scars, with a density of particles approximately 14 times the average of the lung. Similarly, Nielsen et al (2012) observed long-term retention of plutonium in an autopsied Hanford worker (USTUR Case 0269 mentioned above) to be concentrated in parenchymal scar tissue. Some of the fixed deposit of plutonium in the respiratory tract may therefore correspond to plutonium encapsulated in scar tissue.…”
Section: Us Nuclear Workersmentioning
confidence: 84%
“…Measurements of the activity concentration in the BB, bb, and AI regions of the lung of Case 0269 showed uniform distribution between the three regions; the activity concentration in each region was not statistically different from the average lung concentration (Tolmachev et al., 2017). However, autoradiographs of selected lung tissue sections obtained from this donor showed that the microdistribution was non-uniform (Nielsen et al., 2012). An alpha ‘star’ aggregate of plutonium was measured in the connective tissue of the bronchioles, which indicates that the plutonium was localised rather than diffused within the region.…”
Section: Risk Of Cancer From Exposure To Plutoniummentioning
confidence: 99%
“…In its later revision [71], the clearance was suggested to result from a balance between mucociliary transport and blood absorption, and the residual amount should be time-varying. Also, radioactive materials are prone to accumulate in the tracheobronchial lymph nodes [72]; their potential importance in evaluating inhalation hazards has yet to be evaluated. Second, the respiratory system in the VIP-Man phantom is assumed to be a homogeneous mixture of air and water with 0.26 g cc −1 density.…”
Section: Limitationsmentioning
confidence: 99%